Oil-based diaphragm, preparation method thereof and secondary battery

By adjusting the mass ratio and particle size of the first and second binders in the lithium-ion battery separator and adding inorganic fillers, the contradiction between the bonding force and pore formation of the oily separator is solved, and high bonding is achieved The balance of force and good pore formation improves the performance of the battery.

CN119171005APending Publication Date: 2024-12-20HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411128848.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing lithium-ion battery oil-based separators are prone to blockage or poor breathability when improving the bonding force, and it is difficult to take into account both high bonding force and good pore formation.

Method used

Using a coating including the first binder and the second binder, by adjusting its mass ratio and particle size relationship (0.25≤A/B≤4, 0

Benefits of technology

It effectively improves the adhesion and pore formation of the diaphragm, reduces the risk of hole blockage, and improves the ion transfer speed and heat shrinkage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119171005A_ABST
    Figure CN119171005A_ABST
Patent Text Reader

Abstract

The invention relates to an oil-based diaphragm, a preparation method thereof and a secondary battery, the oil-based diaphragm comprises a base membrane and a coating arranged on at least one surface of the base membrane, and the coating comprises a first binder, a second binder and an inorganic filler; the mass ratio of the first binder is A, the mass ratio of the second binder is B, and A and B meet the relation that A / B is larger than or equal to 0.25 and smaller than or equal to 4; the particle size D50 of the first binder is RA, the particle size D50 of the second binder is RB, and RA and RB meet the relation that RA / RB is larger than 0 and smaller than or equal to 0.6. According to the oil-based diaphragm provided by the invention, by controlling the relationship between the particle sizes and the mass ratio of the two binders, the binding power can be effectively improved, the pores of the diaphragm are not easy to block, the ion transfer is accelerated, and the charging and discharging speed is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to an oil-based diaphragm and a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium-ion batteries have been widely used in modern electronic devices due to their excellent properties, such as high specific energy, high specific power, high voltage platform, low self-discharge rate, long cycle life, small environmental impact and no memory effect. They have become an indispensable energy solution in many fields such as mobile phones, computers, electric vehicles, military and space technology. The chemical and physical properties of these batteries provide energy-dense and long-life power sources for portable devices, greatly promoting the development of mobile technology and the electric vehicle industry. Therefore, for the future development of lithium-ion batteries, it is necessary to comprehensively improve the energy density, cycle life and safety performance of lithium-ion batteries, which requires the development of higher-performance diaphragms to match them.

[0003] In recent years, oily functional slurries have begun to be widely used. They have good coating adhesion. Conventional oily slurries often add N-methylpyrrolidone, dimethylacetamide, etc. as organic solvents. Organic functional polymer coated diaphragms have good wettability and liquid retention for electrolytes, can effectively bond diaphragms and pole pieces, increase battery cycle performance, and significantly improve battery safety. However, oily diaphragm coatings with strong adhesion generally have poor porosity and risk of pore plugging. Conversely, coatings with good porosity have insufficient adhesion.

[0004] Therefore, there is an urgent need to develop an oil-based diaphragm that can effectively improve the bonding strength while solving the problems of diaphragm pore blockage and poor air permeability. Summary of the invention

[0005] The purpose of the present invention is to provide an oil-based diaphragm to address the deficiencies of the prior art, which can effectively improve the bonding strength and solve the problems of diaphragm pore blockage and poor air permeability.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] An oil-based diaphragm comprises a base film and a coating disposed on at least one surface of the base film, wherein the coating comprises a first binder, a second binder and an inorganic filler; the mass fraction of the first binder is A, the mass fraction of the second binder is B, wherein A and B satisfy the relationship: 0.25≤A / B≤4; the particle size D50 of the first binder is R A The particle size D50 of the second binder is R B , where R A With R B Satisfy the relationship: 0<R A / R B≤0.6.

[0008] Among them, the first binder mainly controls the degree of pore formation, and the second binder mainly controls the bonding force. If A / B < 0.25, the coating slurry has poor porosity, which will lead to the risk of pore blocking; if A / B > 4, the bonding force of the coating slurry is weak. Therefore, the two need to be set within a certain range to effectively improve the bonding force while solving the problems of pore blocking and poor air permeability of the coating.

[0009] Preferably, the mass fraction of the inorganic filler is C, wherein A, B and C satisfy the relationship: 0.2≤C / (A+B)≤0.55.

[0010] The addition of ceramics can not only reduce costs, but also meet the thermal shrinkage performance of the diaphragm. When C / (A+B) is controlled within the preset range, the thermal shrinkage performance of the coating is good. If C / (A+B) < 0.2, the thermal shrinkage of the oil-based diaphragm will be poor; if C / (A+B) > 0.55, the porosity of the oil-based diaphragm will be poor.

[0011] Preferably, the particle size R of the first binder is A The particle size R of the second binder is 1-120 μm. B 2-200μm.

[0012] Preferably, the molecular weight of the first binder is 300,000-600,000 g / mol, and the molecular weight of the second binder is 600,000-1,000,000 g / mol.

[0013] Preferably, the first binder and the second binder are both selected from one or more of polyvinylidene fluoride, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether copolymer, vinylidene fluoride-propylene fluoride copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and vinylidene fluoride-tetrafluoroethylene copolymer.

[0014] Preferably, the inorganic filler is selected from one or more of aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, boehmite and ceramic fiber.

[0015] In addition, the present invention also provides a method for preparing an oil-based diaphragm for a secondary battery, comprising the following steps:

[0016] S1, uniformly dispersing the inorganic filler in the organic solvent;

[0017] S2, dispersing and dissolving the first binder in the organic solvent in step S1 to obtain a first slurry;

[0018] S3, adding the second binder to the first slurry, and obtaining a diaphragm coating slurry after dispersion and dissolution;

[0019] S4, coating the diaphragm coating slurry on at least one surface of the base film, solidifying and drying, to obtain the oil-based diaphragm of the secondary battery.

[0020] In addition, the present invention also provides a secondary battery, which includes a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, and the separator is the above-mentioned oil-based separator.

[0021] Preferably, the oil-based diaphragm is connected to the positive electrode sheet, and the peel strength between the coating of the oil-based diaphragm and the positive electrode sheet is 10-20 N / m.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] (1) In the present invention, the mass ratio of the first binder and the second binder in the coating of the oil-based diaphragm satisfies the relationship 0.25≤A / B≤4, and the particle size R of the first binder A and the particle size R of the second binder B Satisfying the relationship 0<R A / R B ≤0.6, which can effectively improve the bonding force while not easily clogging the pores of the diaphragm, which is beneficial to accelerate ion transfer and increase the charging and discharging speed.

[0024] (2) The present invention sets the mass fraction C of the inorganic filler to satisfy the relationship: 0.2≤C / (A+B)≤0.55, thereby ensuring that the oil-based diaphragm coating has good porosity and thermal shrinkage performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the oil-based diaphragm prepared in Example 2 of the present invention.

[0026] Figure 2 This is a SEM image of the oil-based diaphragm prepared in Comparative Example 1 of the present invention.

[0027] Figure 3 This is a SEM image of the oil-based diaphragm prepared in Comparative Example 2 of the present invention.

[0028] Figure 4 This is a SEM image of the oil-based diaphragm prepared in Comparative Example 3 of the present invention.

[0029] Figure 5 This is a SEM image of the oil-based diaphragm prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] According to the first aspect of the present application, the present application aims to provide an oil-based diaphragm, comprising a base film and a coating disposed on at least one surface of the base film, wherein the coating comprises a first binder, a second binder and an inorganic filler; the mass fraction of the first binder is A, the mass fraction of the second binder is B, wherein A and B satisfy the relationship: 0.25≤A / B≤4, for example, it can be 0.25, 0.3, 0.5, 0.7, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4. The particle size D50 of the first binder is R A , the particle size D50 of the second binder is R B , where R A With R B Satisfy the relationship: 0<R A / R B ≤0.6, for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6.

[0032] In some embodiments, the base film is one or more of PE, PP, PE / PP composite film, PET, and PI.

[0033] In some embodiments, the mass fraction of the inorganic filler is C, wherein A, B and C satisfy the relationship: 0.2≤C / (A+B)≤0.55, for example, it can be 0.2, 0.3, 0.4, 0.5, 0.55.

[0034] In some embodiments, the particle size R of the first binder is A 1-120 μm, for example, 1 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm; the particle size R of the second binder B It can be 2-200μm, for example, it can be 2μm, 20μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm, or 200μm.

[0035] In some embodiments, the molecular weight of the first binder is 300000-600000 g / mol, for example, 300000 g / mol, 500000 g / mol, 510000 g / mol, 520000 g / mol, 530000 g / mol, 540000 g / mol, 550000 g / mol, 560000 g / mol, 570000 g / mol, 580000 g / mol. the molecular weight of the second binder is 600000-1000000 g / mol, for example, it can be 600000 g / mol, 800000 g / mol, 810000 g / mol, 820000 g / mol, 830000 g / mol, 840000 g / mol, 850000 g / mol, 1000000 g / mol.

[0036] In some embodiments, the first binder and the second binder are both selected from one or more of polyvinylidene fluoride, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and vinylidene fluoride-tetrafluoroethylene copolymer.

[0037] In some embodiments, the inorganic filler is selected from one or more of alumina, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, boehmite, and ceramic fiber.

[0038] According to a second aspect of the present application, the present application aims to provide a method for preparing an oil-based diaphragm of a secondary battery, comprising the following steps:

[0039] S1, uniformly dispersing the inorganic filler in the organic solvent;

[0040] S2, dispersing and dissolving the first binder in the organic solvent in step S1 to obtain a first slurry;

[0041] S3, adding the second binder to the first slurry, and obtaining a diaphragm coating slurry after dispersion and dissolution;

[0042] S4, coating the diaphragm coating slurry on at least one surface of the base film, solidifying and drying, to obtain the oil-based diaphragm of the secondary battery.

[0043] According to a third aspect of the present application, the present application provides a secondary battery, which includes a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, and the separator is the above-mentioned oil-based separator.

[0044] In some embodiments, the oil-based diaphragm is connected to the positive electrode sheet, and the peel strength between the coating of the oil-based diaphragm and the positive electrode sheet is 10-20 N / m.

[0045] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5 O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be modified. The method of modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current. The positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.

[0046] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0047] Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials suitable for use as a negative electrode current collector for lithium-ion batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to copper foil. The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt, and an additive. The electrolyte lithium salt may be LiPF6 and / or LiBOB used in high-temperature electrolytes; it may also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it may also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it may also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent may be a cyclic carbonate, including PC and EC; it may also be a chain carbonate, including DFC, DMC, or EMC; it may also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0048] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0049] Example 1

[0050] Oil-based diaphragm coating slurry

[0051] The coating slurry of the oil-based diaphragm includes a first binder, a second binder and an inorganic filler; the mass fraction of the first binder is A, the mass fraction of the second binder is B, wherein A and B satisfy the relationship: 0.25≤A / B≤4; the particle size D50 of the first binder is R A , the particle size D50 of the second binder is R B , where R A With R B Satisfy the relationship: 0<R A / R B ≤0.6.

[0052] The first binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 600000 g / mol), the mass fraction A of the first binder is 34 parts, and the particle size R of the first binder is A The second binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight is 800000g / mol), the mass fraction B of the second binder is 136 parts, and the particle size R of the second binder is B The inorganic filler is boehmite, and the mass fraction C of the inorganic filler is 40 parts.

[0053] Preparation of diaphragm

[0054] S1, 2.6 kg of inorganic filler is uniformly dispersed in 133 kg of NMP;

[0055] S2, dispersing and dissolving 2.21 kg of the first binder in the NMP in step S1 to obtain a first slurry;

[0056] S3, adding 8.84 kg of the second binder to the first slurry, and obtaining a diaphragm coating slurry after dispersion and dissolution;

[0057] S4, coating the oil-based diaphragm coating slurry on the surface of the PE base film, solidifying and drying, to obtain the oil-based diaphragm of the secondary battery.

[0058] Example 2

[0059] Different from Example 1, in this embodiment, the mass fraction A of the first binder is 85 parts; the mass fraction B of the second binder is 85 parts; and the mass fraction C of the inorganic filler is 40 parts.

[0060] The rest is the same as Example 1 and will not be described again here.

[0061] Example 3

[0062] Different from Example 1, in this example, the mass fraction A of the first binder is 136 parts; the mass fraction B of the second binder is 34 parts; and the mass fraction C of the inorganic filler is 40 parts.

[0063] The rest is the same as Example 1 and will not be described again here.

[0064] Example 4

[0065] Different from Example 1, in this embodiment, the mass fraction A of the first binder is 34 parts; the mass fraction B of the second binder is 136 parts; and the mass fraction C of the inorganic filler is 34 parts.

[0066] The rest is the same as Example 1 and will not be described again here.

[0067] Example 5

[0068] Different from Example 1, in this embodiment, the mass fraction A of the first binder is 115 parts; the mass fraction B of the second binder is 30 parts; and the mass fraction C of the inorganic filler is 80 parts.

[0069] The rest is the same as Example 1 and will not be described again here.

[0070] Example 6

[0071] Different from Example 1, the first binder in this embodiment is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 600000 g / mol), and the particle size R of the first binder is A The second binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight is 850000g / mol), and the particle size R of the second binder is B is 16μm.

[0072] The rest is the same as Example 1 and will not be described again here.

[0073] Example 7

[0074] Different from Example 1, in this embodiment, the first binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 600000 g / mol); the second binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 800000 g / mol); the inorganic filler is alumina, and the mass fraction C of the inorganic filler is 40 parts.

[0075] The rest is the same as Example 1 and will not be described again here.

[0076] Example 8

[0077] Different from Example 1, the first binder in this embodiment is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 500000 g / mol), and the particle size R of the first binder is A The second binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight is 800000g / mol), and the particle size R of the second binder is B It is 15.0μm.

[0078] The rest is the same as Example 1 and will not be described again here.

[0079] Example 9

[0080] Different from Example 2, the mass fraction C of the inorganic filler in this example is 20 parts.

[0081] The rest is the same as Example 2 and will not be described again here.

[0082] Example 10

[0083] Different from Example 2, the mass fraction C of the inorganic filler in this example is 120 parts.

[0084] The rest is the same as Example 2 and will not be described again here.

[0085] Comparative Example 1

[0086] Different from Example 1, this comparative example only contains the first binder and does not contain the second binder. The first binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 600000 g / mol), the mass fraction A of the first binder is 170 parts, and the particle size R of the first binder is A It is 7.1μm.

[0087] The rest is the same as Example 1 and will not be described again here.

[0088] Comparative Example 2

[0089] Different from Example 1, this comparative example only contains the second binder and does not contain the first binder. The second binder is polyvinylidene fluoride-hexafluoropropylene copolymer (molecular weight 800000 g / mol), the mass fraction B of the second binder is 170 parts, and the particle size R of the second binder is B It is 14.5μm.

[0090] The rest is the same as Example 1 and will not be described again here.

[0091] Comparative Example 3

[0092] Different from Example 1, in this comparative example, the mass fraction A of the first binder is 30 parts; the mass fraction B of the second binder is 170 parts; and the mass fraction C of the inorganic filler is 50 parts.

[0093] The rest is the same as Example 1 and will not be described again here.

[0094] Comparative Example 4

[0095] Different from Example 1, in this comparative example, the mass fraction A of the first binder is 170 parts; the mass fraction B of the second binder is 30 parts; and the mass fraction C of the inorganic filler is 50 parts.

[0096] The rest is the same as Example 1 and will not be described again here.

[0097] Comparative Example 5

[0098] Different from Example 1, the first binder in this comparative example is polyvinylidene fluoride (molecular weight is 1000000 g / mol), and the particle size R of the first binder is AThe second binder is polyvinylidene fluoride (molecular weight is 1000000 g / mol), and the particle size R of the second binder is B It is 107μm.

[0099] The rest is the same as Example 1 and will not be described again here.

[0100] The specific parameters of Examples 1-10 and Comparative Examples 1-5 are shown in Table 1 below.

[0101] Table 1

[0102]

[0103]

[0104] The following performance tests were performed on the separators of the secondary batteries prepared in the examples and comparative examples:

[0105] 1. The diaphragms prepared in Example 2, Comparative Examples 1, 2, 3, and 5 were subjected to SEM tests. The test results are shown in Figures 1 to 5 .

[0106] Peel strength test: 1) firstly hot press the adhesive separator and the positive electrode at 1 MPa and 95°C; 2) test the 180° peel strength of the separator and the electrode.

[0107] 2. Diaphragm heat shrinkage test: Set the oven temperature to 110℃, wait until the temperature stabilizes at 110℃, put the oily diaphragm into the oven and keep it for 1 hour, then stop, and test the shrinkage size ratio of the oily diaphragm before and after baking.

[0108] The results of the above performance tests are shown in Table 2 below.

[0109] Table 2

[0110]

[0111]

[0112] It can be seen from the experimental data of Examples 1-10 and Comparative Examples 1-5 in Table 2 that when the mass fraction A of the first binder and the mass fraction B of the second binder satisfy the relationship: 0.25≤A / B≤4, the particle size R of the first binder A and the particle size R of the second binder B Satisfy the relationship: 0<R A / R B When ≤0.6, the porosity of the diaphragm coating can be effectively improved, and the pore uniformity is good, which can accelerate ion transmission and improve adhesion.

[0113] from Figure 1-5It can be seen that the coating of Example 2 has good porosity and high porosity. When only the first binder is contained without the second binder, as shown in Comparative Example 1, the porosity is good but the adhesion is poor. When only the second binder is contained without the first binder, as shown in Comparative Example 2, the porosity of the diaphragm is poor and pores are easily blocked. When the value of A / B is too small, as shown in Comparative Example 3, the pore structure of the diaphragm is small, the porosity is poor, and pores are easily blocked. When the value of A / B is too large, as shown in Comparative Example 4, the adhesion of the diaphragm is poor. When R A / R B When it is too large, as shown in Comparative Example 5, the pore-forming property of the diaphragm is poor and the pores are easily blocked.

[0114] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. An oil-based diaphragm, characterized in that: It comprises a base film and a coating layer provided on at least one surface of the base film, wherein the coating layer comprises a first binder, a second binder and an inorganic filler; The mass fraction of the first binder is A, and the mass fraction of the second binder is B, wherein A and B satisfy the relationship: 0.25≤A / B≤4; The particle size D50 of the first binder is R A The particle size D50 of the second binder is R B , where R A With R B Satisfy the relationship: 0<R A / R B ≤0.

6.

2. The oil-based diaphragm according to claim 1, characterized in that: The mass fraction of the inorganic filler is C, wherein A, B and C satisfy the relationship: 0.2≤C / (A+B)≤0.

55.

3. The oil-based diaphragm according to claim 1, characterized in that: The particle size R of the first binder A The particle size R of the second binder is 1-120 μm. B 2-200μm.

4. The oil-based diaphragm according to claim 3, characterized in that: The molecular weight of the first binder is 300,000-600,000 g / mol.

5. The oil-based diaphragm according to claim 3, characterized in that: The molecular weight of the second binder is 600000-1000000 g / mol.

6. The oil-based diaphragm according to any one of claims 1 to 5, characterized in that: The first binder and the second binder are respectively selected from one or more of polyvinylidene fluoride, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-perfluoromethyl vinyl ether copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, and vinylidene fluoride-tetrafluoroethylene copolymer.

7. The oil-based diaphragm according to any one of claims 1 to 5, characterized in that: The inorganic filler is selected from one or more of aluminum oxide, magnesium oxide, calcium oxide, barium oxide, zinc oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium hydroxide, aluminum hydroxide, boehmite and ceramic fiber.

8. A method for preparing an oil-based separator for a secondary battery according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, uniformly dispersing the inorganic filler in the organic solvent; S2, dispersing and dissolving the first binder in the organic solvent in step S1 to obtain a first slurry; S3, adding the second binder to the first slurry, and obtaining a diaphragm coating slurry after dispersion and dissolution; S4, coating the diaphragm coating slurry on at least one surface of the base film, solidifying and drying, to obtain the oil-based diaphragm of the secondary battery.

9. A secondary battery, characterized in that: It comprises the oil-based diaphragm as described in claims 1-7.

10. The secondary battery according to claim 9, characterized in that It also includes a positive electrode sheet, the oil-based diaphragm is connected to the positive electrode sheet, and the peeling strength between the coating of the oil-based diaphragm and the positive electrode sheet is 10-20N / m.